A Post-Keynesian look at countercyclical monetary policy in dollarized countries: role of endogenous money and liquidity preference theories - Llerena, Grace (2021)
The Post-Keynesian paradigm is the one that has most analyzed the monetary nature of a production economy. In the words of Keynes (1936), fluctuations in effective demand is a monetary problem, with which, this theoretical basis will allow us to understand how monetary processes affect the real sector of the economy, not only in the short term, but particularly, the medium and long term; and, therefore, study the macroeconomic dynamics of countries that do not have their own currency. While Post-Keynesians incorporate endogenous money theory into their analytical framework of 'money, credit, and interest' to explain the configuration of modern monetary policy and the role of central banks, they seem to have forgotten a purely Keynesian category in the monetary debate, the theory of liquidity preference. Therefore, in this document it is proposed to reincorporate in this debate the theory of liquidity preference as a key piece to have a theoretical framework consisting and complete of 'money, credit and interest' that makes it possible to understand the macroeconomic effects of the monetary policy tools in dollarized countries, particularly in times of downturn in the economic cycle.